Folic acid allergy in pregnancy: a case report - Riaz, Azmat; Tabbah, Khaldoun (Journal of the Pakistan Medical Association, 2024)
Folic acid intake prevents neural tube defects in the developing foetus. Folic acid allergy in pregnancy is very rare. Most physicians are unaware of this complication. Only 29 cases of folic acid allergy, mainly in non-pregnant women, have been reported in literature worldwide since 1949. In most reported cases, the involvement of folic acid was confirmed by the absence of symptoms after withdrawing folic acid. We present a case of folic acid allergy in a primigravida. The patient developed severe urticaria within hours of folic acid intake, followed by mild vaginal bleeding. Her symptoms improved within days of stopping folic acid. She delivered a healthy baby at term without anomalies or pregnancy complications. Allergy to folic acid was confirmed postnatally by oral intake of a lower dose of folic acid, where the patient again had urticaria that resolved when the medication was stopped. Keywords: Pregnancy, Folic acid, Allergy.